Køn, krop og ånd i middelalderen - Else Marie Wiberg Pedersen (The Royal Danish Library, 1997)
Very often, the medieval view on "gender" and "body" is depicted either unequivocally negative or just equivocal. According to this simplistic picture, a number of medieval men and women have been portrayed as alternately extremely misogynist and extremely submissive and self-suppressing. With the examples of Bernard of Clairvaux, Beatrice of Nazareth, Mechtild of Hackeborn, and Gertrud of Helfta, this article tries to differentiate more subtly the perception of the concepts "woman/female" and "man/male" by pointing to their function as symbols within the Christian tradition. Furthermore, it is demonstrated that the view on body/soul is not an expression of simple dualism.